Right to Health and Neonatal Surgical Care: Constitutional and Human Rights Perspective - Dhivya, R.; Ramesh, M. (Journal of Neonatal Surgery, 2025)
The Indian Courts have recognized the right to health as a critical component and fundamental for life and it has been universally acknowledged as a basic and fundamental human right under personal life and liberty guaranteed which falls under Article 21 of the Indian Constitution. Newborns with congenital Anomalies are highly dependent upon Neonatal surgical care which ensures survival and quality of life. Despite existing legal provisions Minoritized groups in India often encounter challenges and significant barriers when it comes to access to timely, high standard quality and affordable neonatal surgical treatment. Through Directive principles of state policy and judicial interpretation under Indian Constitution neonatal care is part of the health service since it's the prerogative of the state to ensure it.This paper analyze the role of constitutional provisions, international human rights instruments and emanating judicial interpretation, that highlights the right to neonatal care and comprehensive rights-based legal framework for neonatal surgical care ensuring newborns rights receive not only life-saving surgeries but also post-operative rehabilitation in a just and impartial manner.